Development and validation of questionnaires on perceptions towards covid-19 vaccination and attitude towards covid-19 booster dose vaccination among healthcare workers in Malaysia - Zaid, Siti Nur Aisyah (2024)
Following the end of the COVID-19 pandemic, understanding healthcare workers' perceptions and attitudes toward COVID-19 vaccination and booster doses remains crucial for maintaining high vaccination rates and preparedness for future outbreaks. However, there is a lack of validated instruments to assess the HCWs’ perceptions of COVID-19 vaccination and attitude towards the booster dose. This study aims to develop and validate the COVID-19 Vaccination Perceptions (CoVaP) and Attitude to COVID-19 booster dose vaccination (ACoBV) questionnaires among HCWs in Malaysia. A literature review and discussion with research team members were conducted to identify the content of CoVaP and ACoBV questionnaires. The initial CoVaP is a unidimensional, 12-item scale, while the initial ACoBV was 22 items under 3 domains. The questionnaires underwent a sequential validation process, including content, face, and construct validity. A two-step construct validation process using a cross-sectional study design was conducted sequentially: a) Exploratory Factor Analysis (EFA) using data from 125 HCW, and b) Confirmatory Factor Analysis (CFA) using data from 300 HCW. The study was conducted via both face-to-face and online platforms. First, the EFA analysis of the CoVaP questionnaire revealed seven items with two domains. Subsequent analysis with CFA analysis demonstrated a two-factor model of seven items with an acceptable level of goodness fit indexes (Goodness-of-fit index (GFI) = 0.987comparative fit index (CFI) = 0.999, Tucker- Lewis index (TLI) = 0.999, Normed Fit Index (NFI) = 0.987, chi-squared/degree of freedom (Chi-square/df) = 1.039, and root mean square error of approximation (RMSEA) = 0.011). For the reliability, Cronbach’s alpha coefficient was satisfactory for both domains (0.899 and 0.815). For the ACoBV questionnaire, the EFA analysis showed that two of the 22 items were removed, leaving 20 remaining under three domains. CFA analysis confirmed that the questionnaires were well-constructed. The three-factor model with 16 items had good fit indices (GFI = 0.907, CFI = 0.965, TLI = 0.946 and NFI = 0.931). The internal consistency for the ACoBV was good according to Cronbach alpha coefficients 0.905, 0.941 and 0.859 for three domains. In conclusion, the CoVaP and ACoBV questionnaires are valid and reliable tools for measuring HCWs' perceptions of COVID-19 vaccination and attitudes toward COVID-19 booster dose vaccination. However, since these are the newly developed questionnaires in Malaysia to asses the issue, an actual study needs to be conducted in the future to know the exact outcomes of these perceptions and attitudes of the HCWs towards COVID-19 vaccines and the booster dose.